The Influence of Convenience and Security on Brand Loyalty among DANA Syariah Users: The Mediating Role of Brand Trust - Naufal Luthfi Alifa; Diana Djuwita; Abdul Fatakh; Syed Muhammad Abdul Rehman Shah (JOURNAL OF ISLAMIC ECONOMICS AND BUSSINES ETHICS, 2025)
This study examines the influence of convenience and security on brand loyalty, mediated by brand trust, among Muslim college students using the DANA digital wallet. In the Islamic fintech context, where ethical values intersect with technological adoption, trust and loyalty are key to user retention. Although DANA offers strong usability and security, it trails competitors in loyalty, raising the question: how do convenience and security affect brand loyalty through brand trust among users familiar with Islamic economic principles? This research is significant as it connects conventional consumer behavior with Islamic economic perspectives, focusing on a demographic familiar with sharia-based financial principles. Using a quantitative approach, the study analyzed survey data from 100 purposively sampled students at the Faculty of Sharia and Islamic Economics, IAIN Syekh Nurjati Cirebon. All of them are DANA users for over three months. Findings revealed that convenience and security significantly influence brand trust. Brand trust fully mediates the impact of convenience and partially mediates the impact of security on brand loyalty. These results highlight that while functionality is important, trust, especially when aligned with Islamic ethical values, is crucial in fostering loyalty. To improve user retention, digital wallet providers should enhance not only technical performance, but also ethical guarantees rooted in transparency and fairness, as emphasized in Islamic economics.